2011
DOI: 10.1139/p11-078
|View full text |Cite
|
Sign up to set email alerts
|

Intermittency and erraticity of charged particles produced in 28Si-Ag/Br interaction at 14.5 A GeV

Abstract: In this paper, we present the intermittency and the erraticity analyses of the distributions of charged particles produced in 28 Si-Ag/Br interaction at incident energy 14.5 A GeV. The experimental results are compared with a Monte Carlo simulation using ultra-relativistic quantum molecular dynamics (UrQMD) model. The experimental data show the presence of a nonstatistical component in the produced charged-particle density. Neither the UrQMD simulation nor the purely statistical simulation was found to match t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…As the simulated data do not exhibit any anisotropy in the (η, ϕ) plane, subsequently we did not extend our self-affine analysis to the (UrQMD+BEC) case. We should mention that all experimental β q values are also several times larger than the intermittency indices (φ q ) obtained in the (1d) analysis of the same set of data [17]. It has been argued [29] that the phase-space density of multiparticle production is anisotropic, and the upward bending in the SFM plot is a direct consequence of this anisotropy.…”
Section: Methodology and Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…As the simulated data do not exhibit any anisotropy in the (η, ϕ) plane, subsequently we did not extend our self-affine analysis to the (UrQMD+BEC) case. We should mention that all experimental β q values are also several times larger than the intermittency indices (φ q ) obtained in the (1d) analysis of the same set of data [17]. It has been argued [29] that the phase-space density of multiparticle production is anisotropic, and the upward bending in the SFM plot is a direct consequence of this anisotropy.…”
Section: Methodology and Resultsmentioning
confidence: 80%
“…Very recently, we have performed a (1d) analysis of a set of 28 Si-Ag/Br data at an incident energy of 14.5A GeV [17], where the experimental measurements are compared with a set of simulated data based on the UrQMD code [18]. We observed that the experimental intermittency strength in the azimuthal (ϕ) space is approximately twice as large as that in the η-space, while the UrQMD model produces negligible intermittency in both spaces.…”
Section: Introductionmentioning
confidence: 99%
“…In one such analysis [30] the MF-DFA method is adopted to construct the multifractal spectrum of shower track distribution in Au + Au collision at 200A GeV, but without comparing the experiment with any simulation. (solid circles) [32,34], the G q moment (open circles) and the T q moment (solid triangles) analysis [35,36]. Left panel: 28 Si + Ag/Br interaction at 14.5A GeV and right panel: 32 S + Ag/Br interaction at 200A GeV.…”
Section: Resultsmentioning
confidence: 99%
“…(15). Corresponding D q values obtained from Hwa's technique of G q moments, Takagi's technique of T q moment [35] and the SFM [32] are also plotted together. Separate diagrams are drawn for the UrQMD data to avoid mutual overlapping of the points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation